EFEITO DA SAZONALIDADE HÍDRICA NA QUALIDADE DO LENHO DE ÁRVORES DE EUCALIPTOS - Oliveira, Jean Carlos Lopes de (2021)
The interaction between tree and climate influences the annual growth, wood density, and vessels and fibers morphology. However, this complex relationship still has questions to be answered, mainly for species widely cultivated in Brazil, such as Eucalyptus urophylla and Eucalyptus grandis. The objective was to evaluate the annual growth, wood density and vessels and fibers morphology in earlywood and latewood, to characterize the behavior of two eucalyptus clones in a rainfall seasonality gradient, identifying the relationships with wood properties and, finally, to indicate the most representative sample of the radial profile of these properties. Growth ring width, apparent density and, vessel and fiber morphology were studied radial direction (pith to bark) of Eucalyptus urophylla (G7) and Eucalyptus grandis (Q8), in five sites with different climatic seasonality in Brazil. The latewood of the most contrasting sites in the rainfall seasonality showed lower densities. The earlywood had twice more hydraulic conductivity than the latewood. The greatest increment in the growth rings was shown to have a decreasing effect on the wood density of both clones. In addition to the fibers wall thickness, the density can be explained by growth ring width and potential hydraulic conductivity. Sampling in the range of 33 to 66% of the radius represented satisfactorily the general average of the apparent density, length and fiber thickness wall and vessels diameter of E. urophylla and E. grandis wood.